Amodiaquine‐induced reproductive toxicity in adult male rats. Issue 2 (17th December 2015) - Niu, Yan‐Ru; Wei, Bing; Chen, Bi; Xu, Li‐Hua; Jing, Xia; Peng, Cai‐Ling; Ma, Tian‐Zhong
SUMMARY: Amodiaquine (AQ) is routinely prescribed as an anti‐malarial drug. Here, we evaluated AQ‐induced toxicity in the male reproductive system. Eighty adult male Sprague‐Dawley rats were randomly divided into four groups that received distilled water (control) or daily doses of 5 mg/kg body weight, 10 mg/kg, or 15 mg/kg AQ for 2 weeks. Testes morphology was analyzed using hematoxylin‐and‐eosin staining, terminal dUTP nicked‐end labeling (TUNEL), and immunostaining whereas protein expression was determined by Western blotting. AQ dose‐dependently led to abnormal spermatogenesis. Disruption of the blood‐testis barrier and increased germ cell apoptosis were observed in all three AQ‐treated groups. Interestingly, AQ‐induced damage of spermatogenesis recovered over time, based on the survival of promyelocytic leukemia zinc‐finger (PLZF)‐positive, undifferentiated spermatogonia. Serum levels of luteinizing hormone and testosterone, as well as testicular testosterone levels, were not significantly altered in AQ‐treated groups compared with controls. Collectively, our study suggests that AQ exerts substantial acute side effects on the reproductive systems of adult male rats by inducing the apoptosis of differentiating spermatogenic cells and disruption of blood‐testis barrier function. Mol. Reprod. Dev. 83: 174–182, 2016. © 2015 Wiley Periodicals, Inc .